OR06-6 Whole-Exome Sequencing of Patients with Pituitary Stalk Interruption Syndrome (PSIS) Reveals Probably Pathogenic Variants in Novel Candidate Genes. - Correa, Fernanda (J Endocr Soc, 2019)
Background: Pituitary Stalk Interruption Syndrome (PSIS) is characterized by the presence of a thin or absent pituitary stalk, usually associated with an ectopic posterior pituitary, hypoplasia of the anterior pituitary and pituitary hormone deficiencies. The identification of pathogenic variants in novel genes has clinical implications for the management of the patients and genetic counseling. Objective: to identify pathogenic variants in patients with PSIS using whole-exome sequencing (WES) (trio approach). Method: We performed whole exome sequencing in eleven patients (trio approach) with PSIS using Agilent Sure Select and Illumina NextSeq technology. The patients had been screened for genes previously associated to hypopituitarism by Sanger or Target gene panel. We searched for pathogenic variants considering de novo, homozygous, compound heterozygous and X- linked inheritance. Results: We identified 116 rare allelic variants (excluding synonymous) located in exons or splice sites: 47 de novo, 20 homozygous, 48 compound heterozygous and 1 X-linked. All variants were expressed in pituitary and/or hypothalamus. Of these, 11 variants were highlighted because the genes had correlation to malformations of central nervous system, midline defects or hormonal deficiencies: LCMT1, PCDHB14, ATXN1, ATXN7, KRT18, SYNE1, WDR27, CC2D2A, HAUS5, IFT140 and ELF4. Among them, five were de novo: two were found in genes associated to cleft palate (LCMT1 and KRT18), two in genes previously associated to neurological phenotype (ATXN7 and ATXN1), one in a gene related to organization of neural cadherin-like cell adhesion (PCDHB14).ELF4 was X-linked and was previously associated with isolated growth hormone deficiency. Conclusion: The WES identified 11 potentially pathogenic variants in new candidate genes for PSIS.